Grammatical information and conceptual metaphors : the case of anger - Stanojević, Mateusz-Milan (Array, 2014)
Recent discourse-based and corpus based studies on conceptual metaphors show that the way in which a conceptual metaphor is expressed may have an impact on the metaphor in question. In other words, metaphor is not only a conceptual but also a linguistic phenomenon. This paper explores the interface between conceptual and linguistic information on the example of the concept of ANGER. More specifically, we look into four common English anger-related nouns (anger, wrath, fury and rage), and the (potential) metaphoricity of five grammatical constructions in which they appear: premodification by adjective (e.g. deep anger), predicative qualification (e.g. anger was palpable), noun-of-anger-related noun construction (outburst of anger, eruption of rage), the anger-related noun as the first participant of a predicate (e.g. anger flared, rage subsided), and the anger-related noun as the second participant of a predicate (e.g. vent anger, express rage). Each of the five constructions has a widely different percentage of potentially metaphorical expressions. We show that these differences are a result of a number of local factors: the conceptual characteristics of each grammatical construction (modeled using cognitive grammar), the conceptual make-up and the folk model of the ANGER, the salience of the terms used for the concept, the conceptual characteristics arising from other morphosemantically related terms, their history, and ecological factors. Despite the comprehensive nature of such an approach, it does not overlook the locality of metaphor (as argued in the discourse-based approaches). Moreover, grammar is a natural way of unifying conceptual and discourse-based approaches to metaphor, because looking at grammatical issues does not threaten the primary focus either approach: grammar is conceptual as well as usage-based.